Phytochemical Composition and Potential Genotoxic effects of Important Egyptian Medicinal Plants - Rashed, Khaled; Anthonissen, Roel; Cappoen, Davie; Verschaeve, Luc (Pharmacognosy Communications)
Introduction: We performed a phytochemical analysis and investigated the potential genotoxic properties of ten different methanol extracts of plants that are frequently used in Egypt for medicinal purposes. Such studies are important because these plants were never thoroughly investigated with respect to their possible potential sideeffects and risks for humans. Materials and Methods: In this study we used the bacterial Vitotox test and alkaline comet assay in human C3A cells to estimate their genotoxic potential. The Vitotox test is an interesting screening test which correlates very well with the well-known Ames assay but has the advantage of being rapid, sensitive and requiring only small amounts of a test compound. The test was conducted in the presence and absence of a metabolizing S9-enzyme fraction. The comet assay is now a widely used and validated genotoxicity test which can be applied in all DNA-containing cells. In this study it was conducted in human C3A cells which conserved phase I and II biotransformation capabilities. The in vitro NRU assay was used to investigate toxicity and utilized as a dose-finding test. Results: None of the plants have shown genotoxic properties although one of them, Derris rubusta, showed borderline genotoxicity in both tests. This plant also contains alkaloids and coumarins, besides flavonoids, carbohydrates, tannins and triterpenes that were also found in the other plants. Conclusion: So far all 10 investigated medicinal plants appeared not genotoxic but due to borderline effects, Derris robusta deserves further complementary investigations.
Keywords: Alkaline comet assay; Egyptian medicinal plants; Methanol extracts; Phytochemical analysis; Vitotox test